2013
DOI: 10.1136/gutjnl-2013-305302
|View full text |Cite
|
Sign up to set email alerts
|

PTEN antagonises Tcl1/hnRNPK-mediated G6PD pre-mRNA splicing which contributes to hepatocarcinogenesis

Abstract: These results establish the counteraction between PTEN and Tcl1 as a key mechanism that regulates the PPP and suggest that targeting the PTEN/Tcl1/hnRNPK/G6PD axis could open up possibilities for therapeutic intervention and improve the prognosis of patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 25 publications
3
93
0
2
Order By: Relevance
“…Meanwhile, genes that are associated with the production and utilization of antioxidants, including NADPH, glutathione, and thioredoxin, have been implicated in HCC. Glucose 6 phosphate dehydrogenase, a critical enzyme in the pentose phosphate pathway generating NADPH, has been shown to be overexpressed in HCC in a PTEN-dependent manner (41). Overexpression of thioredoxin and thioredoxin-related REDOX molecules, glutaredoxin and peroxiredoxin, was documented in HCC and was associated with increased proliferative output, aggressive clinicopathologic parameters, presence of metastasis, and poor prognosis in HCC patients (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, genes that are associated with the production and utilization of antioxidants, including NADPH, glutathione, and thioredoxin, have been implicated in HCC. Glucose 6 phosphate dehydrogenase, a critical enzyme in the pentose phosphate pathway generating NADPH, has been shown to be overexpressed in HCC in a PTEN-dependent manner (41). Overexpression of thioredoxin and thioredoxin-related REDOX molecules, glutaredoxin and peroxiredoxin, was documented in HCC and was associated with increased proliferative output, aggressive clinicopathologic parameters, presence of metastasis, and poor prognosis in HCC patients (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The development and progression of HCC is a complicated process that involves the deregulation of multiple genes that are essential for cell biological processes (14,15). Previously, a distinct choline transporter called the SLC44A1-5 family was shown to be present in various human cancer cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo imaging showed that lung metastasis was found in 0 of 6 mice and 1 of 6 mice in the 2 MTHFD1L-knockdown groups as opposed to its occurrence in 5 of 6 mice from the NTC group ( Figure 8B). Histological analysis suggested that tumors derived phate pathway (PPP), was overexpressed in HCC owing to the inactivation of PTEN (33). Malic enzymes were overexpressed in human HCC (34) and were found to be repressed by p53 in osteosarcoma cells (35).…”
Section: Inhibition Of the Folate Cycle Represses Hcc Growth And Sensmentioning
confidence: 99%